The Moderating Role of Debt-to-Equity Ratio on the Impact of Price-to-Earnings Ratio and Return on Equity on Firm Value: Evidence from the Properties and Real Estate Sector - Wulandari, Febi; Hariyanto, Dedi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study uses an associative quantitative method to analyze the relationship between the independent variables (Price Earning and Return On Equity) and the moderating variable (Debt to Equity Ratio) on the dependent variable (firm value) in the Property & Real Estate sector listed on the Indonesia Stock Exchange during the period 2020-2022. The normality test results show a data distribution that is close to normal, while the multicollinearity, autocorrelation, heteroscedasticity, and linearity tests do not reveal significant problems in the data used. Regression analysis shows that Debt to Equity Ratio has a significant influence on firm value, especially when considered alongside moderating variables such as Debt to Equity Ratio. These findings provide a deeper understanding of the factors that influence firm value in the Property & Real Estate sector in Indonesia. Overall, this study makes a significant contribution to understanding capital market dynamics and the factors that influence firm value in a sector that is crucial to the country's economic growth. The implications of the findings can serve as a basis for better decision-making in the financial management of companies in the Property & Real Estate sector, as well as a guide for further research in this area.